Multi-Sectoral Uses of Water & Approaches to DSS in Water Management in the NOSTRUM Partner Countries of the Mediterranean - Khaled Abu-Zeid; Sameh Afifi (Fondazione Eni Enrico Mattei (FEEM), 2006)
Agriculture contributes an average of about 10% to the GDP of the partner countries of the Mediterranean involved in the project NOSTRUM. On the other hand, industry contributes an average of about 30% in these countries. It is to remark that in almost all countries the weight of industry accounts between 20% and 30% of the national economy, with the exception of Algeria, where this weight is at about 60%, mainly imputable to the great development of oil extraction and energy sector. In the majority of participating countries, agriculture sector is the greatest consumer of water (more than 65% of total water consumption). Although the case from France where agriculture water use is only about 10% of total water consumption and Italy with around 45%, but this may be due to the fact that most countries reporting for their agricultural water consumption do not include the amount of rain-fed to cultivated lands as a part of their agriculture water use. Most agriculture water use is limited to irrigation water from streams/rivers and groundwater. Rain-fed cultivated-lands in France is almost 90% of its total cultivated area. For Croatia, data given in National Report indicate a 0% of water use for agriculture. The average of water use for agriculture for all the basin is of 62.3% but with a great scatter expressed by a high standard deviation (26.8%) that reflects a wide variation range of water use for agriculture among different countries. The average of water use for agriculture is weakly less on northern countries (52.7%) than on southern countries (75.2) but the twice values are still on the range of the average of the all basin and cannot be taken as indication of difference between north and south. Integrated Water Resources Management (IWRM) plans are currently developed and implemented by various countries to organize the multi-sectoral water uses. On the other hand, the need for Decision Support System (DSS) as a tool in developing and implementing Integrated Water Resources Management (IWRM) is in growing demand. In spite of the great potential for the research and the development of DSS, the utilization of DSS in water management is not widely spread in the partner countries. In some countries, DSS was planned and developed at the scale of territorial integrated water management. Integration of DSS application to the existing IWRM systems at the partner countries would assist in satisfying the water related Millennium Development Goals (MDGs).
Keywords: O21; Q01; Q25; 330; Integrated Water Resources Management; Decision Support Systems; Mediterranean Basin